2022
DOI: 10.1038/s41598-021-04570-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the surgical outcomes of Baerveldt glaucoma implant for open-angle glaucoma, an age-related eye disease

Abstract: To identify the factors associated with the surgical outcomes of Baerveldt glaucoma implant (BGI) for open-angle glaucoma (OAG), the medical records of 51 consecutive OAG patients (age, 43–91 years) who underwent BGI were retrospectively reviewed (median follow-up, 21.7 months). Surgical success was defined as the following postoperative intraocular pressures (IOPs, mmHg): (A) 6 ≤ IOP ≤ 21; (B) 6 ≤ IOP ≤ 18; and (C) 6 ≤ IOP ≤ 15 without loss of light perception or additional glaucoma surgery. Univariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It might be difficult to control an IOP ≤ 17 mmHg in eyes that have been subjected to prior intraocular surgeries. Moreover, younger age was linked to an increased risk of surgical failure for criterion B and C. Previous reports also suggested that younger age was a risk factor for failure of BGI surgery 7,8,13 . As previously mentioned, the wound healing process by active fibroblasts may be associated with surgical failure of BGI.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It might be difficult to control an IOP ≤ 17 mmHg in eyes that have been subjected to prior intraocular surgeries. Moreover, younger age was linked to an increased risk of surgical failure for criterion B and C. Previous reports also suggested that younger age was a risk factor for failure of BGI surgery 7,8,13 . As previously mentioned, the wound healing process by active fibroblasts may be associated with surgical failure of BGI.…”
Section: Discussionmentioning
confidence: 91%
“…9 . Other studies with small sample sizes reported the surgical results of BGI separately for each type of glaucoma [10][11][12][13][14][15] . The present study is unique because it examined 204 eyes of Japanese patients with different types of glaucoma and evaluated the long-term surgical outcome of BGI (350-mm 2 endplate) surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age increased the risk of surgical failure for all criteria in our study, which is consistent with the ndings of previous studies on tube-shunt surgery. 17,[24][25][26][27] Age-related impairments in wound healing have been associated with broblast dysfunction, whereas younger age has been associated with a more robust wound healing response. [28][29][30] The wound healing process involving active broblasts may play a role in the surgical failure of ltering surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our secondary outcomes are to investigate the association between a history of SGTV and postoperative results, as well as to identify postoperative complications. Additionally, we examined the changes in IOPs and medication scores in eyes affected by ATTRv amyloidosis that required LEC at different time points: baseline, 1 year, 3 years, and 5 years after LEC 30 . These alterations were evaluated in response to LEC and subsequent surgical interventions performed to reduce IOP.…”
Section: Methodsmentioning
confidence: 99%